INTERNALISASI NILAI MODERASI BERAGAMA MELALUI EKSTRAKURIKULER ROHANI ISLAM DI SMA NEGERI 13 SEMARANG - Maulidin, Syarif; Dwi Firma, Yuyun; Arkanudin, Ari (JURNAL KAJIAN ISLAM MODERN, 2025)
This research focuses on the analysis of Islamic spiritual extracurricular activities at SMA Negeri 13 Semarang, exploring their role in shaping students' religious character, tolerance, and social harmony. The main purpose of this article is to evaluate how these extracurricular activities contribute to the internalization of religious moderation, particularly in a pluralistic society like Indonesia. The research is motivated by the growing importance of fostering tolerance and preventing radicalism through educational programs. The study employs qualitative methods, including observation, interviews with teachers, and document analysis of extracurricular activities. The hypothesis is that Islamic spiritual extracurriculars enhance students' religious understanding and promote interfaith cooperation. The findings reveal that activities such as weekly religious studies (ta‘lim/kiss), community services like mosque cleaning, and interfaith charity work significantly improve students' understanding of moderation, tolerance, and social responsibility. Furthermore, these activities contribute to a positive school culture that strengthens unity among students of different religious backgrounds. This research contributes to the broader field of education by demonstrating how extracurricular programs can be effectively used to promote religious moderation and prevent radicalization. In conclusion, the study emphasizes the vital role of extracurricular activities in fostering a balanced and tolerant mindset among students, making a significant contribution to peace-building and social harmony in schools.